2014
DOI: 10.3748/wjg.v20.i30.10585
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of controlled attenuation parameter for liver steatosis in patients with chronic hepatitis B

Abstract: CAP is a novel tool that can be used to assess the degree of steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…This study confirms, on a series of Romanian patients, the preliminary results of previous studies [20,[22][23][24][25][26][27][28][29][30][31], namely that, among all histopathological parameters assessed during various diffuse liver diseases, CAP is independently influenced only by the amount of steatosis, not by fibrosis, necroinflammatory activity, ballooning or lobular inflammation (quantified according to liver disease etiology). The CAP value increased alongside the increase in the steatosis degree.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study confirms, on a series of Romanian patients, the preliminary results of previous studies [20,[22][23][24][25][26][27][28][29][30][31], namely that, among all histopathological parameters assessed during various diffuse liver diseases, CAP is independently influenced only by the amount of steatosis, not by fibrosis, necroinflammatory activity, ballooning or lobular inflammation (quantified according to liver disease etiology). The CAP value increased alongside the increase in the steatosis degree.…”
Section: Discussionsupporting
confidence: 89%
“…In all patients, steatosis was estimated by visual assessment as a percentage of hepatocytes with fatty accumulation; to be able to pool all patients, steatosis was converted into the following grading system: S0: steatosis in less than 10% of hepatocytes, S1: 11%-33%, S2: 34%-66% and S3: 67%-100% of hepatocytes, a system which was also used in other studies [12,20,22,24,26,27]. The histological type of steatosis was specified, as pure macrovesicular, mixed (i.e.…”
Section: Histological Studymentioning
confidence: 99%
See 1 more Smart Citation
“…To solve this problem, a novel non‐invasive procedure of NAFLD diagnosis has been developed, the controlled attenuation parameter (CAP). The CAP is quantitated by transient elastography (TE) and has been proven to be a substitute for ultrasonography and liver biopsy in epidemiological investigations of NAFLD …”
Section: Introductionmentioning
confidence: 99%
“…The controlled attenuation parameter (CAP) is a recently developed quantitative, objective NIT for liver steatosis assessment, which measures the attenuation of ultrasound waves transmitted at a known frequency in the liver parenchyma . The CAP values are obtained simultaneously to LSM using the same device, and the estimation of liver fat through this method is reliable . The CAP values of 215 to 238 dB/m hold a high sensitivity for the detection of steatosis in patients with chronic liver disease of different etiologies, and in one study CAP and proton magnetic resonance spectroscopy showed comparable accuracy for the detection of hepatic steatosis in patients …”
mentioning
confidence: 99%